Czeska Partia Piratów jako nowe ugrupowanie w systemie partyjnym Republiki Czeskiej = The Czech Pirate Party as a new political party in the party system of the Czech Republic - Koźbiał, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the Czech Pirate Party as a new political party on the party scene of the Czech Republic. It was established in 2009, but it enetered the Chamber of Deputies of the parlament in 2017. Currently, it is the third political force in it. Initially, the party, being a component of the international pirate movement, in its program postulated the use of new computer techniques in democratic settlements, limiting patent and copyright rights, or ensuring anonimity in social media.
Keywords: Republika Czeska; Czeska Partia Piratów; nowe partie polityczne; czeski systempartyjny; Czech Republic; Czech Pirate Party; new political parties; Czech party system